THE INFLUENCE OF GLOBALIZATION ON THE TEACHING STYLES OF GEOGRAPHY TEACHERS IN INDONESIA - Imam Mahdi; Sriyanti Sriyanti; Agung Hidayat; Novika Adi Wibowo (STKIP Singkawang, 2025)
Abstract. This study aims to analyze the impact of globalization on the teaching style of geography teachers in Indonesia. The main focus of this research is to identify the extent to which globalization influences four key parameters in teaching: technology adaptation, multiculturalism, global literacy and skills, and educational standards and evaluation. The method used is a survey involving 100 geography teachers from 19 provinces in Indonesia, who assessed their responses to these parameters using a Likert scale. The regression analysis results show that globalization has a significant impact on teaching styles, with a regression coefficient of 0.7486, meaning that every increase in adaptation to globalization enhances the teaching style by 0.7486 units. The R² value of 60.40% and the adjusted R² of 58.78% indicate that around 60% of the variation in teaching style can be explained by the influence of globalization. These findings suggest that globalization encourages teachers to integrate technology into their teaching, promote multicultural values, and apply international educational standards. This study concludes that the influence of globalization on teaching styles in Indonesia is substantial and fosters an improvement in the quality of geography education.Keywords: Globalization, Teaching Style, Geography Teachers